Analysis of Public-Private Partnership in Providing Primary Health Care Policy: An Experience From Iran - Gharaee, Hojatolah (J Prim Care Community Health, 2019)
Background: This study aims to analyze the public-private partnership (PPP) policy in primary health care (PHC), focusing on the experience of the East Azerbaijan Province (EAP) of Iran. Methods: This research is a qualitative study. Data were gathered using interviews with stakeholders and document analysis and analyzed through content analysis. Results: Participants considered political and economic support as the most important underlying factors. Improving system efficiency was the main goal of this policy. Most stakeholders were supporters of the plan, and there was no major opponent. Implementing the health evolution plan (HEP) was an opportunity to design this policy. Participants considered the lack of provision of infrastructure as the main weakness, changing the role of the public sector as the main strength, and promoting social justice as the main achievement of policy. The results of the quantitative data review showed that following the implementation of this policy, health indicators have been improved. Conclusions: Based on the results of this study, the PPP model in EAP is a new and successful experience in PHC in Iran. Supporting and developing this policy may improve the quality and quantity of providing care.